2020
DOI: 10.7189/jogh.10.011101
|View full text |Cite
|
Sign up to set email alerts
|

The role of children in transmission of SARS-CoV-2: A rapid review

Abstract: The role of children in transmission of SARS-CoV-2: A rapid review Background Understanding the role of children in the transmission of SARS-CoV-2 is urgently required given its policy implications in relation to the reopening of schools and intergenerational contacts. MethodsWe conducted a rapid review of studies that investigated the role of children in the transmission of SARS-CoV-2. We synthesized evidence for four categories: 1) studies reporting documented cases of SARS-CoV-2 transmission by infected chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
142
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(158 citation statements)
references
References 21 publications
6
142
1
6
Order By: Relevance
“…A number of authors have concluded that children and adolescents may be less susceptible to SARS-CoV-2, 2,14 although there are multiple sources of bias in each study type, which can complicate straightforward analysis. In contact-tracing studies, testing of only symptomatic contacts will introduce significant bias, as will seroprevalence studies drawn from clinical contact studies (eg, primary care) or residual laboratory sera.…”
mentioning
confidence: 99%
“…A number of authors have concluded that children and adolescents may be less susceptible to SARS-CoV-2, 2,14 although there are multiple sources of bias in each study type, which can complicate straightforward analysis. In contact-tracing studies, testing of only symptomatic contacts will introduce significant bias, as will seroprevalence studies drawn from clinical contact studies (eg, primary care) or residual laboratory sera.…”
mentioning
confidence: 99%
“…Importantly, a systematic meta-analysis of different cohort studies observed that asymptomatic patients with COVID-19 seems to correlate with young age and social activity [76,77]. In particular, future studies aiming to understand the contribution of young aged patients such as children to asymptomatic transmission of SARS-CoV-2 should be prioritised [78]. In summary, the prevalence of asymptomatic SARS-CoV-2 infection and duration of pre-symptomatic infection are not well understood, as asymptomatic individuals are not routinely tested.…”
Section: Epidemiological Relevance Of Asymptomatic Sars-cov-2 Casesmentioning
confidence: 99%
“…8 In contrast, the disease trajectory of COVID-19 in children is typically mild, and children may be less likely to be infected or infect others. 9 Therefore, while surveillance for pediatric spread of COVID-19 remains important to guide plans for school and daycare reopening, the health effects of COVID-19 in children is expected to be much lower than in older individuals.…”
Section: A Population Perspectivementioning
confidence: 99%